Derivación de valores económicos de la Producción de leche de bovinos en el Cantón Saquisilí utilizando funciones de beneficio. - Cuvi Chuquimarca, Romel Santiago (2022)
The present project was developed in the Canton Saquisilí, province of Cotopaxi. It is about the study of the derivation of economic values of the production of bovine milk using benefit functions in order to implement an appropriate program of Genetic Improvement. The methodology was applied by socializing the project to the producers in the area, data collection, and records such as the cost of production, milk density, bovine weight intakes, a mastitis test which was made using the California Mastitis test (CMT), takings of the weight of the milk in kilograms and the measurement of the land in hectares in which their livestock live. Once finished the project showed that only 28 bovine producers in the area participated with 98% of cows which 61.6% are involved in the production of milk. The results also showed that 17.2% are cows, 14.1% are pregnant, 4% are lactating, 1% are dry bovines and only 2% are male bovines. It is important to mention that none of them had productive records, reproductive costs, and production costs. On the other hand, the density of milk from a 25% of the cows achieved the established parameters of 1028 to 1033 g/ml contributing a good quality of fat in it. 88.2% of the cows had no somatic cells in the CMT test, evidencing good health of the quarters of the udder. It was also evidenced that the minority of the cows produce from 15 to 18 liters per day and the rest of cows produce between 2 to 7 liters per day. Consequently, this work showed that many of the producers do not have an adequate management of the dairy production system, however, this project is a baseline to take genetic selection criteria, associated with the economic utility of cattle production systems. The selection criteria that was taken into account in the Saquisili Canton are the daily weight gain because there are animals that consume little and generate more, the density of the milk because there are bovines that give ranges equal or more than the requested parameters and the liters of milk produced per day.